Life habits of postmenopausal women: Association of menopause symptom intensity and food consumption by degree of food processing. (February 2022) - Noll, Priscilla Rayanne e Silva; Noll, Matias; Zangirolami-Raimundo, Juliana; Baracat, Edmund Chada; Louzada, Maria Laura da Costa; Soares Júnior, José Maria; Sorpreso, Isabel Cristina Esposito
Highlights: In this study of postmenopausal women, most of the caloric intake was from fresh and minimally processed foods. Higher consumption of vegetables was associated with lower intensity of vasomotor symptoms and better quality of life. Intake of ultra-processed foods was associated with more intense vasomotor and sexual symptoms. Intakes of sugar-sweetened beverages and sausage were related to greater intensity of somatic symptoms and worse memory and concentration. Worse self-rated health, obesity, and comorbidity increased symptom intensity. Older age and higher education were protective against menopausal symptoms. Abstract: Objective: To evaluate in postmenopausal women the association between menopause symptom intensity and the quality of life and clinical, anthropometric, and lifestyle factors, focusing on food consumption by degree of processing. Study design: A cross-sectional study of 288 postmenopausal women using interviews. Main outcome measures: The Kupperman-Blatt Menopausal Index and the Women's Health Questionnaire were used to evaluate the main outcomes of menopausal symptom intensity and quality of life, respectively. Data on socioeconomic, clinical, anthropometric, and lifestyle variables (smoking, alcohol intake, physical activity, and food consumption) were collected. Results: Most women had moderate to severe intensity of menopausal symptoms. The highest tertile of ultra-processed food consumption was associated with a greater intensity of vasomotor symptoms (prevalence ratio [PR] 0.73, 95% confidence intervals [CI] 0.55–0.96) and sexual behavior (PR 1.22, CI 1.01–1.49). Higher intakes of sugar-sweetened beverages and sausages were associated with somatic symptoms (PR 1.23, CI 1.01–1.49) and poorer memory/concentration (PR 1.22, CI 1.02–1.47/ PR 1.22, CI 1.01–1.48). The highest tertile of vegetable intake was associated with greater protection against depressive mood (PR 0.64, CI 0.43–0.96), vasomotor symptoms (PR 0.79, CI 0.63–0, 99), and sleep disorders (PR 0.83, CI 0.69–0.99), and better quality of life (PR 0.79, CI 0.62–0.99). Conclusion: More intense vasomotor, sexual, somatic, and memory and concentration symptoms are associated with a higher consumption of ultra-processed foods, whereas those with a higher consumption of vegetables reported lower menopause symptom intensity and a better quality of life.